Detection of Circulating Tumor Cells in Renal Cell Carcinoma: Disease Stage Correlation and Molecular Characterization - Klezl, Petr; Pospisilova, Eliska; Kolostova, Katarina; Sonsky, Jindrich; Maly, Ondrej; Grill, Robert; Pawlak, Ireneusz; Bobek, Vladimir (Journal of clinical medicine, 2020)
The presence of circulating tumor cells (CTCs) in patients with solid tumors is associated with poor prognosis. However, there are limited data concerning the detection of CTCs in renal cell cancer (RCC). The aim of this study is to evaluate the presence of CTCs in peripheral blood of patients with RCC undergoing surgery (n = 186). CTCs were tested before and after surgery as well as during the follow-up period afterwards. In total 495 CTC testing in duplicates were provided. To enrich CTCs, a size-based separation protocol and tube MetaCell® was used. CTCs presence was evaluated by single cell cytomorphology based on vital fluorescence microscopy. Additionally, to standardly applied fluorescence stains, CTCs viability was controlled by mitochondrial activity. CTCs were detected independently on the sampling order in up to 86.7% of the tested blood samples in patients undergoing RCC surgery. There is higher probability of CTC detection with growing tumor size, especially in clear cell renal cell cancer (ccRCC) cases. Similarly, the tumor size corresponds with metastasis presence and lymph node positivity and CTC detection. This paper describes for the first-time successful analysis of viable CTCs and their mitochondria as a part of the functional characterization of CTCs in RCC.
Keywords: renal cancer; culturing; immunotherapy; in vitro; gene expression; MetaCell; CTCs; PDL-1